Analisis Karakteristik Alterasi Pada Daerah Tolotio Kecamatan Bonepantai Kabupaten Bone Bolango - Rachman, Arianzah Rizki; Kasim, Muhammad; Akase, Noviar (Journal of Applied Geoscience and Engineering, 2024)
The research location is in the Tolotio area, Bonepantai District, Bone Bolango Regency. This study aims to analyze the characteristics of alteration in the research area. There are a total of 30 random samples taken from outcrops at the research location, using the geological mapping method and geochemical analysis (X-Ray Diffraction) XRD. The results of the study in the form of geomorphological conditions are divided into three morphological units, namely intrusion hill units, steep-sloping volcanic hills and alluvial plain units. The stratigraphy in the research area is divided into three rock units, namely porphyry diorite rock units, crystal tuff rock units and alluvial sediment units. The geological structure of the research area is in the form of faults and fractures, where the fault is a left normal slip fault to the right with a plane structure value of N130 ° E / 56 ° while the line structure is N257 ° E / 44 ° and a rake value of 47 ° and tension fractures that have the main stress orientation direction of northeast - southwest. The alteration types in the research area are divided into four types of alteration, namely propylitic alteration type, phyllic alteration type, argillic alteration type and advanced argillic alteration type.